Hosting capacity enhancement study for a distribution network implementing BESS from the DIgSILENT PowerFactory module (2024)
The growing demand for energy services and resources in Colombia implies a short and long-term modification of the injected power into the grid. In the case of solutions for immediate scenarios, it gives way to tools oriented towards distributed generation (DG) as a solution to variations in demand. However, this involves considering the calculation of the new system capacity in such a way that its stability, reliability, and supply performance are maintained without violating restrictions or requiring an expansion of the distribution network. It is here that Hosting Capacity seeks to satisfy the increasing demand by bringing the generation of nodes closer to their upper voltage limits. Thus, a high value of this parameter indicates a tolerance capacity for new loads without exceeding operating limits. This document studies one of the most effective methods for enhancing Hosting Capacity to indicate a clear path in scenarios of power injection and consumption into a distribution system to maintain performance to the maximum. This methodology consists of a battery system connected through an inverter to the node (secondary substation) to be treated. With this consideration, in the face of frequency or voltage disturbances, this system will act as a battery or storage, depending on the DER or SPARE case, respectively. The study requires the use of the DIgSILENT PowerFactory software analyzed from embedded Python language and DPL (DIgSILENT Powerfactory Language).